Temporary Explant of a Transcutaneous Bone Conduction Hearing Implant for Imaging of the Pituitary Gland. Issue 7 (August 2018) - Roesch, Sebastian; Kugler, Anton; Schlattau, Alexander; Rasp, Gerd
Abstract : Objective: Clinical report on feasibility and outcome of a surgical procedure. Patient: Nine-year-old child, supplied with a transcutaneous bone conduction hearing implant, requiring magnetic resonance imaging of the head to exclude a tumor of the pituitary gland. Intervention: Temporal removal and subsequent reimplantation of the implant in a single surgical procedure. Main Outcome Measure: Postoperative audiometric results. Conclusion: Under specific clinical circumstances, temporary removal of the transcutaneous bone conduction implant described, is technically accomplishable.